Thomas Hobbes and Political Theory - Dietz, Mary G. (University Press of Kansas, 1990)
This volume explores, from a variety of perspectives, the political theory of the man who is arguably the greatest English political thinker. It is the first substantial collection of new, critical essays on Thomas Hobbes by leading scholars in over a decade.Hobbes's writings stirred debate in his own lifetime, for two centuries thereafter, and continue to do so in ours. They emerged in a period of intense political turmoil-a time of civil war and regicide, of puritanical rule and royal restoration. "They were motivated," Dietz argues, "by concrete political problems and a practical concern, namely, to secure political order, absolute sovereignty, and civil peace." The contributors emphasize and answer a series of expressly political questions that, to date, have not been fully addressed in the Hobbes literature. They contend that Hobbes's writings are not mere static artifacts of a particular historical milieu, but rather rich sources of a variety of interpretations and criticisms that spur discussion and debate in their turn.